Optimalisasi Potensi Akademik Siswa SDN 3 Kranggan melalui Lomba Cerdas Cermat dan Gerak Lokomotor - Janah, Karunia Eka Nafilatul; Asista, Windi; Leti, Alexander Piku; Madu, Anita Sriyanti Novi; Kolo, Aprilia Vindi; Resa, Maharani Rambu Bangi; Makin, Agnes Rohana; Kaha, Marlin; Wiwi, Daniel Japa; Hakim, Lukman (Pakis Journal Institute, 2026)
Learning innovations that are able to create a fun, challenging and meaningful learning atmosphere for elementary school students are needed so that the academic potential and motor skills of elementary school students can be maximally encouraged. This community service activity aimed to optimize the academic potential and basic motor skills of students at SDN 3 Kranggan through quiz competitions and locomotor movement activities. The program was implemented using a participatory and educational approach involving students and teachers in a series of structured academic and physical activities. The quiz competition focused on improving students’ cognitive abilities, teamwork, and self-confidence, while locomotor movement activities were designed to develop gross motor skills through sack race, running, and jumping exercises. The results showed increased learning motivation, active participation, improved collaboration among students, and better mastery of basic locomotor skills. These findings indicate that integrating academic competition with physical activities can serve as an effective strategy to support holistic development of elementary school students.